ECONOMIC PROFICIENCY : THE NEXT LEVEL OF LITERACY IN DIGITAL AGE - Riani, Lilia Pasca; Manik, Yuni Mariani; Puspitaningrum, Yuliastuty; Pangestika, Ratna Rosita (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
As we transition into the digital age, mastering economics becomes essential for navigating its opportunities and challenges. Economic proficiency involves effectively using economic concepts and terminology. This study aims to explore the key elements of economic proficiency, addressing the gap in detailed research on this critical skill set. This research design is a literature review with descriptive research type and qualitative approach. Data were obtained from a review of relevant previous research published in 86 national and international journals and official websites of credible institutions. Data analysis was carried out in 4 stages, 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusion. The results showed that detected economic proficiency construct was conducted by 4 variables, 1) financial literacy was composed of 8 indicators, 2) economic literacy consisted of 8 indicators, 3) managerial literacy was formed by 7 indicators, and 4) decision-making and problem-solving consisted of 6 indicators.